Female Genital Tract Microbiota Affecting the Risk of Preterm Birth: What Do We Know So Far? A Review. Issue 7 (July 2020) - Tsonis, O.; Gkrozou, F.; Harrison, E.; Stefanidis, K.; Vrachnis, N.; Paschopoulos, M.
Abstract : (Abstracted from Eur J Obstet Gynecol Reprod Biol 2020;245:168–173) Spontaneous preterm birth (sPTB) is a major cause of neonatal morbidity and mortality worldwide. The literature has suggested that vaginal microbiota and its genome, known as the microbiome, may play a role in regulating the maternal immune response that induces early labor.